Geology : A Very Short Introduction - Zalasiewicz, Jan (New York Oxford University Press, 2018)
Jan Zalasiewicz introduces the field of geology, its fundamental role in understanding the Earth and other planets, and its economic importance in the finding and exploitation of resources. He explains how geologists work today, and describes major discoveries such as plate tectonics, and the field's exciting frontiers such as the geology of Mars.
Include Illustrations and Index
Keywords: Geology -- Earth sciences